Impact of cropping pattern on growth, yield attributes and system productivity of citronella (Citronella winterianus) - pulses intercropping system in Central India - ANSARI, M H; VERMA, B K; ANSARI, M A; MISHRA, DUSHYANT; SRIVASTAVA, A K; KHAN, NAUSHAD; SAQUIB, MOHD. (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur during 2010-11 and 2011-12 to study the Impact of cropping pattern on growth, yield attributes and system productivity of citronella (Citronella winterianus L.) - pulses intercropping system in Central India. There was significant superiority in growth, yield attributes and yield of sole cropping as compared to their intercropping. On an average significantly higher herbage yield of first (202.74 q/ha) and second cutting (161.15 q/ha) was recorded in citronella sole cropping followed by 2:1 row ratio of citronella + pigeonpea. However, the citronella sole cropping gave significantly highest citronella equivalent oil yield and net returns than other cropping systems. The higher B: C ratio was recorded under citronella: pigeonpea 2:2 row ratio (12.6) in 2010-11 and citronella: pigeonpea (2:1) (8.75) in 2011-12 than other cropping systems. The higher LER values in citronella: pigeonpea intercropping, i.e.1.03 to 1.08, clearly indicate 3 to 8% advantage over their sole stand. Citronella sole recorded the highest crop profitability (Rupees753 to 837 ha/day).